2012
DOI: 10.4161/onci.1.1.18073
|View full text |Cite
|
Sign up to set email alerts
|

EGFR inhibitors, MHC expression and immune responses : Can EGFR inhibitors be used as immune response modifiers?

Abstract: A recent study from our laboratory demonstrated that epidermal growth factor receptor (EGFR) inhibitors (EGFRIs) augment the expression of class I and class II MHC molecules. This finding provides an additional mechanism through which EGFRIs may exert anti-tumor effects and supports the notion that EGFRIs may influence adaptive immune responses by altering immune gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…For example, it has recently been demonstrated that BRAF V600E inhibitors can increase the expression of MDAs, block the production of immunosuppressive cytokines such as IL-1α/β, and increase the recruitment of CD8 + T cells into tumors 17 , 37 , 38 . Indeed, it is becoming apparent that—in spite of the fact that the driving force behind the development of these therapeutic approaches had little to do with tumor immunology—the impact of targeted therapies on the expression of immune regulators may directly influence antitumor immune responses 39 . Our data also suggest that—in addition to providing a growth advantage to tumor cells—the genetic amplification of BRAF V600E may also promote tumor cell immune escape by attenuating the baseline expression levels of MHC Class I molecules.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has recently been demonstrated that BRAF V600E inhibitors can increase the expression of MDAs, block the production of immunosuppressive cytokines such as IL-1α/β, and increase the recruitment of CD8 + T cells into tumors 17 , 37 , 38 . Indeed, it is becoming apparent that—in spite of the fact that the driving force behind the development of these therapeutic approaches had little to do with tumor immunology—the impact of targeted therapies on the expression of immune regulators may directly influence antitumor immune responses 39 . Our data also suggest that—in addition to providing a growth advantage to tumor cells—the genetic amplification of BRAF V600E may also promote tumor cell immune escape by attenuating the baseline expression levels of MHC Class I molecules.…”
Section: Discussionmentioning
confidence: 99%
“…ErbB receptors belong to a transmembrane tyrosine kinases receptor family that includes four members: the epidermal growth factor (EGF) receptor (EGFR; ErbB1), ErbB2 (HER2), ErbB3 (HER3), and ErbB4 (HER4) 15 . One possible mechanism that has been described to explain MHC‐I inhibition is the induction of the EGFR pathway 16 , 17 . This mechanism has been widely investigated in several infectious pathologies, autoimmunity and tumors 16 , 17 .…”
mentioning
confidence: 99%
“…In immunocompromised mice xenografted with human tumors, this activity obviously reflects cancer cell-intrinsic (or stromal) mechanisms. As a matter of fact, mTORC1 is hyperactivated (hence delivering critical pro-survival signals) in a large number of malignancies, most often due to genetic or epigenetic alterations that result in constitutive signaling via upstream tyrosine kinase receptors (e.g., the epidermal growth factor receptor, EGFR) [64-67]. Conversely, the anticancer effects of rapalogs in immunocompetent settings appear to rely, at least in part, on the elicitation of tumor-targeting immune responses.…”
mentioning
confidence: 99%